Jewish American literature since 1945 : an introduction - Wade, Stephen (Edinburgh University Press, 1999)
The author "offers a student guide to the major writiers, their key works and their cultural and philosophical backgrounds. The theoretical underpinnings of the literature -- including the postmodern, the master narrative and metafiction -- are also introduced in an accessible form. The themes, issues and philosophies of writers including Saul Bellow, Erica Jong, Arthur Miller, Cunthia Ozick, Phillip Roth and Isaac Bashevis Singer are inter-related and wider literary and historical topics are alluded to and explained. Covering women's writing, novels, poetry, drama and belles-lettres, the author offers a comprehensive and readable survey of the achievements of an important group of writers in twentieth-century American literature."--Back cover